Heritage of history knowledge - Sagatova, A.S. (KU publ., 2020)
The development and prosperity of any country goes hand in hand with the education of its descendants. The source of this knowledge and education were samples of ancient oral literature and works of great personalities. The harmony of wisdom and morality, the essence of which is combined with educational and cognitive qualities, leads everyone to a deep thought, spiritual heights, aspirations for the future, the education of consciousness, intelligence, attention. Such spiritual values are based on eloquence, wisdom, wisdom of ancestral traditions, which in terms of high understanding and cunning have penetrated into the hearts of future generations and will be remembered forever. The great ideals are intertwined with the values of the Kazakh worldview, which have always been the basis for the development of the country's history. The author aims to study the role and place of national wisdom in the formation of the worldview in the modern context, the development of time. He informs the next generation that it is important to remember that people of each historical epoch were inspired by the desire for the future of their country, awakened their eyes and foreshadowed new breakthroughs in public life. The symbols of national outlook, as moral wise examples, should deepen the field of human thinking in the world of virtues - the way to the perfection of his soul. The achievements of traditional Kazakh culture testify to this. The fact that our ancestors lived a harmonious life in harmony with the steppe nature shows that it reflects the horizons of his thinking. The author believes in the revival of the spiritual world in a perfect society.
Төл тарихты тану мұрасы
Наследие познания истории
Keywords: art of wisdom; high moral; horizons of knowledge; ethical values; country interests; spiritual freedom; high intelligence; achieve happiness; legacy of wisdom; historical memory; school of wisdom; life experience; instill humanism; virtue; humanist educator; national ethics